Why Is It So Hard to Evaluate Knowledge Exchange?; Comment on "Sustaining Knowledge Translation Practices: A Critical Interpretive Synthesis" - Kathryn Oliver (Kerman University of Medical Sciences, 2023)
Despite a growth in knowledge translation (KT) or exchange activities, and a smaller growth in their evaluations, it remains challenging to identify evidence of efficacy. This could be due to well-documented political and logistical difficulties involved in evaluating knowledge exchange interventions. By bringing in theory from science and technology studies (STS), Borst et al1 offer a new way of thinking about this problem. Most KT evaluations draw on health research traditions; centralising comparability, efficacy, and so on. Borst et al propose focusing on the work it takes to move knowledge over boundaries between these communities, seeing relationships as interactions, not just conduits for evidence. They show how 'context' can be understood as a mutual creation, not a static environment; and that institutions shape behaviours, rather than merely being sites or platforms for evidence mobilisation. Seeing KT as a creative, active practice opens new ways to design and evaluate KT mechanisms.